SCIENTIFIC PRODUCTION IN LABOR RELATIONS AND PEOPLE MANAGEMENT (2000/2017) - Gemelli, Catia Eli; Mendonça Fraga, Aline; Amaral Prestes, Vanessa (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The connections between Work Relationships and People Management are inevitable, since both involve interactions in the work context. This study aimed to map the scientific production of the areas indexed in the Web of Science (WoS) database from 2000 to 2017. From a quantitative-descriptive bibliometric analysis, it was examined the behavior of the national and international literature in relation to its temporal distribution, by language and periodicals, as well as frequency of authorship and keywords. The main results are: expressive growth in publications; predominance of English-language journals and journals from the United Kingdom and North America; and prevalence of English as the mother language of the main authors. The subjects highlighted were: relations with trade unions, innovation and studies focused on countries with economies in expansion (in the international context); labor market, sustainability, culture and organizational climate, diversity, expatriation (in the national context).